Optimizing Vocational Teacher Performance Through Sustainable Management - Tine Yuliantini; Mochamad Soelton; Eri Marlapa; Paijan Paijan; Martarina Indah (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: Creating graduates who have tall significance to the requirements of the work showcase, can proceed to higher education, and are able to make employments through business, is the most commitment of the establishment and school group. Endeavors to overcome deterrents in accomplishing these objectives must be overcome with different focused on and modified breakthroughs by realizing the vision, mission, objectives, and areas of work that have been sought after based on the conditions and potential they have. Clarifying its role in progressing human asset advancement, preparing teachers with fundamental abilities and information to realize the SDGs, and building compelling, responsible, and comprehensive instructive.Purpose: This study seeks to examine and evaluate the influence of the relationship between the Influence of Transformational Leadership, Compensation, and Organizational Culture on Teacher Performance in Moderating Job SatisfactionDesign/methodology/approach: The sampling technique uses saturated samples, which are taken from the entire population The information used is essential information collected employing a survey disseminated to 124 changeless establishment teachers. The analysis method uses the Structural Positive and Partial Least Square Equation Model (SEM). Findings/Results: Transformational leadership encompasses a positive but inconsequential impact on teacher performance, organizational culture, compensation, and job satisfaction have a noteworthy positive impact on teacher performance. Job satisfaction can moderate some of of the compensation on teacher performance. Job satisfaction can moderate the effect of transformational leadership on teacher performance as a predictor. And job satisfaction can moderate some of the effect of organizational culture on teacher performance.Conclusion: Organizations have to be take steps to decrease the state of mind of teachers who are not ideal in looking at the authority side of this school, arrangements are advertised to make strides communication, transparency in organizational management, and maintain equity in approaches. This will increment by and large employee job satisfaction.Originality/value (State of the craftsmanship): This investigate not as it were looks at the coordinate relationship between organizational culture, Compensation and Transformational Leadership on Teacher Performance but moreover considers the directing role of Job Satisfaction. This appears that the relationship between undetectable esteem factors, counting brain research within the working environment, is much more complex than it appears. Keywords: transformational leadership, compensation, organizational culture, teacher performance, job satisfaction, sustainable development goals (sdgs)